Philosophy of Naturalism - Ferdiana, Roswinda Maria (Journal of Innovation in Teaching and Instructional Media, 2023)
Naturalistic philosophy is an approach in philosophy that emphasizes observation and understanding of natural phenomena and human life through a scientific lens. This research aims to explore the importance of learning naturalistic philosophy in the context of the development of knowledge and human understanding of the surrounding world. Learning naturalistic philosophy opens the door to a broad understanding of the interconnectedness between humans and nature. By grasping the basic principles of naturalism, individuals can develop an awareness of the natural processes that shape their existence. This provides a strong foundation for understanding science and technology, as well as strengthening analytical skills and problem-solving abilities. The existence of naturalistic philosophy also supports the concepts of sustainability and environmental preservation. Through a profound understanding of human interaction with nature, individuals can develop a responsible attitude toward the environment and contribute to the conservation of natural resources. The importance of learning naturalistic philosophy is also reflected in its ability to stimulate curiosity and creativity. By engaging in philosophical thinking related to naturalism, one can develop a critical perspective on complex issues and formulate innovative solutions. This journal employs literature analysis and exploration of key concepts in naturalistic philosophy. The results indicate that learning naturalistic philosophy not only provides profound insights into nature and life but also shapes individuals who think analytically, are environmentally responsible, and are creative in addressing contemporary challenges. Therefore, the integration of naturalistic philosophy into education is a crucial step forward.